2020
DOI: 10.1002/jcop.22399
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of depression in women with chronic disease: Evidence from a sample of poor loan takers from Pakistan

Abstract: Depression is one of the most common mental health problems in Pakistani women, with prevalence rates estimated to be above 30%. Identification of the determinants of depression in chronically ill, poor, and debt‐ridden women of the country is a neglected area. A quantitative survey using standardized tools was used to sample women from across Pakistan. It was found that women had higher odds of depression when they (a) perceived unfavorable self‐health, (b) had less health decision‐making power, (c) encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This may be because women have less social support and face more stigma in Pakistani society when they suffer from a chronic disease [ 52 ]. Furthermore, women may also have more fears and anxiety when facing chronic disease burden due to their inability to continue care and nurturing for family, children, and other dependents [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because women have less social support and face more stigma in Pakistani society when they suffer from a chronic disease [ 52 ]. Furthermore, women may also have more fears and anxiety when facing chronic disease burden due to their inability to continue care and nurturing for family, children, and other dependents [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, women may also have more fears and anxiety when facing chronic disease burden due to their inability to continue care and nurturing for family, children, and other dependents [50].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding health service quality, some scholars believed that it was directly related to disease hazards. For example, Jafree ( 16 ) applied bivariate regression analysis and found that when health service was insufficient or dissatisfied, patients would face greater depression. Arabyat and Raisch ( 17 ) described that the health service quality of diagnosis and assessment by healthcare providers was an important part of the care of patients with chronic obstructive pulmonary disease, and contributed to improving functioning and overall health-related quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%